Tombs of the ancient Americas - Bendick, Jeanne (New York : F. Watts, 1993)
Examines how archaeologists discover ancient burial tombs, and the secrets these tombs reveal about the cultures of such Indian civilizations as the Moche, Quipus, Mayas, Aztecs, and Anasazi.
Includes bibliographical references (p. 61) and index.
Keywords: Indians; Tombs -- America; Indians; Tombs -- America; Archaeology